Gluconacetobacter diazotrophicus AZ0019 requires functional nifD gene for optimal plant growth promotion in tomato plants - Pallucchini, Michele; Franchini, Martina; El-Ballat, Enas M.; Narraidoo, Nathalie; Pointer-Gleadhill, Benjamin; Palframan, Matthew J.; Hayes, Christopher J.; Dent, David; Cocking, Edward C.; Perazzolli, Michele; Fray, Rupert G.; Hill, Phil J. (Frontiers in Plant Science, 2024)
Gluconacetobacter diazotrophicus is a nitrogen fixing bacterium able to colonise a wide range of host plants and is marketed as a biofertiliser due to its ability to promote plant growth. This study aims to investigate how biological nitrogen fixation (BNF) competency affects the growth promotion of inoculated tomato plants and to describe the colonisation mechanism of this bacterium in dicot systems. A nitrogen fixation impaired mutant (Gd nifD-) was produced by disrupting the nifD gene, which encodes the nitrogenase Mo-Fe subunit, in order to assess its plant growth promotion (PGP) capability in comparison to G. diazotrophicus wild type strain (Gd WT). Furthermore, tagged strains were employed to monitor the colonisation process through qPCR analyses and fluorescence microscopy. Following a preliminary glass house trial, Gd WT or Gd nifD- were applied to hydroponically grown tomato plants under nitrogen-replete and nitrogen-limiting conditions. Bacteria reisolation data and plant growth parameters including height, fresh weight, and chlorophyll content were assessed 15 days post inoculation (dpi). Gd WT significantly enhanced plant height, fresh weight, and chlorophyll content in both nitrogen conditions, while Gd nifD- showed a reduced PGP effect, particularly in terms of chlorophyll content. Both strains colonised plants at similar levels, suggesting that the growth advantages were linked to BNF capacity rather than colonisation differences. These findings indicate that a functional nifD gene is a fundamental requirement for optimal plant growth promotion by G. diazotrophicus.